PEMBUATAN MEMBRAN PEMBALUT LUKA YANG MENGANDUNG ALFA MANGOSTIN DAN UJI AKTIVITAS ANTIBAKTERI TERHADAP Staphylococcus aureus dan Staphylococcus epidermidis - B A Martinus (Jurnal Katalisator, 2020)
A research has been done on the antibacterial activity test alpha mangostin with a concentration of 0.5 %, 1 % and 2% of the wound dressings membrane. Wound dressings membrane is used to cover and protect new system or wounds from bacteria. One of xantone compounds which possess antibacterial activity, namely alpha mangostin were isolated from the skin of the mangosteen. Wound dressings membrane contains of alpha mangostin, starch yam, polyvinyl alcohol, propylene glycol, nipagin, nipasol and aquadest. The membrane evaluation of wound dressings include organoleptic examination, the membrane thickness, the pH test, moisture proofing, water vapor transmission rate test, elongation percent test and tensile strength, swelling test and test activity against Staphylococcus aureusand Staphylococcus epidermidis. The wound dressings membrane suitable alpha mangostin characterization that is F1. Antibacterial activity test was performed using the diffusion method on Muller Hilton Agar media. The test results of antibacterial activity of alpha-mangostin in the membrane of the best wound dressing is F3 the diameter of inhibition zone against S. aureus is 10,67 mm and against S. epidermidis is 11.33 mm. Based on analysis of one-way ANOVA using SPSS 20.0 obtained significant value that is P <0.05. Duncant test of S. aureus results showed that F2 and F3 with Comparative (Daryant Tulle®) does not have significant differences and against of S. epidermidis results showed that F3 with Comparative (Daryant Tulle ®) does not have significant differences.